2020
DOI: 10.32615/ps.2020.057
|View full text |Cite
|
Sign up to set email alerts
|

Subtle changes in solar radiation under a green-to-red conversion film affect the photosynthetic performance and chlorophyll fluorescence of sweet pepper

Abstract: Although spectrum conversion films are used to improve the photosynthetic efficiency and, ultimately, crop growth, the effects of the modified spectrum on photosynthetic traits in plants have not yet been sufficiently reported. The objective of this study was to investigate the changes in photosynthetic performance and chlorophyll fluorescence of sweet pepper (Capsicum annuum L.) under a green-to-red conversion (GtR) film. The GtR-modified spectrum increased the dry mass and decreased the petiole length. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…On the one hand, an increase in respiration intensity may indicate an increase in growth processes associated with the accumulation of biomass; on the other hand, increased respiration activity is a sign of stress in plants. Previously, in a series of works by different scientific groups, it was shown that relatively small changes in the lighting spectrum of plants caused by photoconversion covers have a significant effect on both the productivity of plants and the intensity of physiological processes in them [26][27][28][29][30]33,35,36,55,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105], which correlates with our data.…”
Section: Supplementary Materialssupporting
confidence: 91%
“…On the one hand, an increase in respiration intensity may indicate an increase in growth processes associated with the accumulation of biomass; on the other hand, increased respiration activity is a sign of stress in plants. Previously, in a series of works by different scientific groups, it was shown that relatively small changes in the lighting spectrum of plants caused by photoconversion covers have a significant effect on both the productivity of plants and the intensity of physiological processes in them [26][27][28][29][30]33,35,36,55,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105], which correlates with our data.…”
Section: Supplementary Materialssupporting
confidence: 91%
“…Before making assumptions about the reasons for the positive effect of the PCF, it should be noted that the passing of light through glass coated with luminescent nanopar-ticles was not accompanied by a noticeable increase in the intensity of the visible range. However, in the present work, as well as in a number of other works, an increase in plant productivity was demonstrated [25][26][27][28][29][30][31][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Nanosized particles can act as a protectant against UV owing to their capability to absorb and scatter ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 70%
“…For example, the absorbance of a spectral conversion film decreased by 11% without nano-oxide filters or by 2–8% with nano-oxide filters after one year of exposure to sunlight [ 12 ]. In contrast, exposure to the sun for 49 days reduced the conversion efficiency of a film by only 0.2%, indicating that the film was relatively stable [ 75 ]. In addition to longevity, a barrier to commercial implementation of spectral conversion films is the cost to purchase, install, and maintain them in a greenhouse setting.…”
Section: Discussionmentioning
confidence: 99%